Clinico-genomic Characterization of ATM and HRD in Pancreas Cancer: Application for Practice - Park, Wungki; O'Connor, Catherine A; Bandlamudi, Chaitanya; Forman, Daniella; Chou, Joanne F; Umeda, Shigeaki; Reyngold, Marsha; Varghese, Anna M; Keane, Fergus; Balogun, Fiyinfolu; Yu, Kenneth H; Kelsen, David P; et al. (Clinical cancer research, 2022)
Characterizing germline and somatic ATM variants (gATMm, sATMm) zygosity and their contribution to homologous recombination deficiency (HRD) is important for therapeutic strategy in pancreatic ductal adenocarcinoma (PDAC). Clinico-genomic data for patients with PDAC and other cancers with ATM variants were abstracted. Genomic instability scores (GIS) were derived from ATM-mutant cancers and overall survival (OS) was evaluated. Forty-six patients had PDAC and pathogenic ATM variants including 24 (52%) stage III/IV: gATMm (N = 24), and sATMm (N = 22). Twenty-seven (59%) had biallelic, 15 (33%) monoallelic, and 4 indeterminate (8%) variants. Median OS for advanced-stage cohort at diagnosis (N = 24) was 19.7 months [95% confidence interval (CI): 12.3-not reached (NR)], 27.1 months (95% CI: 22.7-NR) for gATMm (n = 11), and 12.3 months for sATMm (n = 13; 95% CI: 11.9-NR; P = 0.025). GIS was computed for 33 patients with PDAC and compared with other ATM-mutant cancers enriched for HRD. The median was lower (median, 11; range, 2-29) relative to breast (18, 3-55) or ovarian (25, 3-56) ATM-mutant cancers (P < 0.001 and P = 0.003, respectively). Interestingly, biallelic pathogenic ATM variants were mutually exclusive with TP53. Other canonical driver gene (KRAS, CDKN2A, SMAD4) variants were less frequent in ATM-mutant PDAC. ATM variants in PDAC represent a distinct biologic group and appear to have favorable OS. Nonetheless, pathogenic ATM variants do not confer an HRD signature in PDAC and ATM should be considered as a non-core HR gene in this disease.